Crystal structure of bis{N-methyl-N′-[3-(4-methoxyphenyl)-1-methylpropane-1-ylidene]carbamohydrazonothioato}zinc(II), C26H36N6O2S2Zn - Tan, Ming Yueh; Kwong, Huey Chong *; Crouse, Karen A.; Ravoof, Thahira Begum S. A.; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C26H36N6O2S2Zn, triclinic, P1̄ (no. 2), a = 9.1777(5) Å, b = 12.3828(7) Å, c = 13.3137(7) Å, α = 102.157(5)°, β = 101.395(4)°, γ = 100.771(4)°, V = 1408.14(14) Å3, Z = 2, Rgt(F) = 0.0489, wRref(F2) = 0.1147, T = 100(2) K.